Pengaruh Status Sosial Siswa Terhadap Hasil Belajar Sosiologi Kelas X SMA - Al Hidayah, Riama (Jurnal Pendidikan Sosiologi dan Humaniora, 2013)
This research aimed to investigate the impact of social status on sociology learning outcomes in X SHS class. While research method used was a descriptive survey study form. Data collection tool that used was interviews, questionnaires and documentation. Data processing technique is to test the validity and reliability testing of the questionnaire, to see social status tested by percentage. While to look at the effect of social stastus tested through a simple linear regression with SPSS 17. Regression coefficient social status variables (X) is 0.75 x. This means that any increase in the social status of 1, then the learning outcomes will be increased by 0.75 and R2 value of 0.08, meaning that the influence of social status on learning outcomes was 0.8%.Key Words: Impact, Social Status, Learning Outcomes.